Idiopathic Distal Sensory Polyneuropathy and Fibromyalgia Syndrome: A Comparative Phenotyping Study - Jamie Burgess; Anne Marshall; Leandros Rapteas; David Riley; Kohei Matsumoto; Cheng Boon; Alia Alchawaf; Maryam Ferdousi; Rayaz A. Malik; Andrew Marshall; Stephen Kaye; David Gosal; et al. (Pain and Therapy)
Abstract Introduction Painful idiopathic distal sensory polyneuropathy (IDSP) and fibromyalgia syndrome (FMS) are cryptogenic chronic pain syndromes. The contribution of small fibre pathology (SFP) in FMS remains controversial. This study aims to quantify small nerve pathology in participants with IDSP and FMS and identify relationships of SFP with sensory phenotypes. Methods In this study, 73 individuals (FMS: 25, IDSP: 23, healthy volunteers: 25) underwent comprehensive assessment, including neurological exams, questionnaires, sensory tests, and corneal confocal microscopy. Results IDSP participants displayed lower wind-up ratio (WUR) relative to FMS (p < 0.001), loss of function to thermal and mechanical stimuli and elevated neuropathy disability scores compared to FMS and healthy volunteers (all p < 0.001). FMS participants demonstrated gain of function to heat and blunt pressure pain responses relative to IDSP, and healthy volunteers (heat: p = 0.002 and p = 0.003; pressure: both p < 0.001) and WUR (both p < 0.001). FMS participants exhibited reduced corneal nerve fibre density (p = 0.02), while IDSP participants had lower global corneal nerve measures (density, branch density, and length) relative to healthy volunteers (all p < 0.001). Utilising corneal nerve fibre length, SFP was demonstrated in 66.6% of participants (FMS: 13/25; IDSP: 22/23). Conclusion Participants with SFP, in both FMS and IDSP, reported symptoms indicative of small nerve fibre disease. Although distinctions in pain distributions are evident between individuals with FMS and IDSP, over 50% of participants between the two conditions displayed both a loss and gain of thermal and mechanical function suggestive of shared mechanisms. However, sensory phenotypes were associated with the presence of SFP in IDSP but not in FMS.